Comparison of the latanoprost 0.005%/timolol 0.5% + brinzolamide 1% versus dorzolamide 1%/timolol 0.5% + latanoprost 0.005%: a 12-week, randomized open-label trial - Kanamoto T (Dove Medical Press, 2012)
Shunsuke Nakakura1, Hitoshi Tabuchi1, Yukio Baba2, Futoshi Maruiwa2, Nobuko Ando2, Takashi Kanamoto3, Yoshiaki Kiuchi31Department of Ophthalmology, Saneikai Tsukazaki Hospital, Himeji, Hyogo Prefecture, Japan; 2Department of Ophthalmology, Baba Eye Clinic, Hiroshima, Japan, 3Department of Ophthalmology and Visual Sciences, Graduate School of Biomedical Sciences, Hiroshima University, Hiroshima City, JapanObjective: To compare the safety and effectiveness of fixed-combination regimes (latanoprost–timolol and brinzolamide 1% compared to dorzolamide 1%/timolol and latanoprost) in open-angle glaucoma patients after switching from a combination of three topical antiglaucoma eye drops.Methods: We conducted an open, randomized 12-week multicenter prospective study. We randomly allocated 39 patients who had been treated with three antiglaucoma eye drops (prostaglandin F2α analogues plus beta-blockers and carbonic anhydrase inhibitors) into two groups. Group A (n = 20) were treated with latanoprost–timolol and brinzolamide 1% therapy and Group B (n = 16) were treated with dorzolamide 1%/timolol and latanoprost. Thirty-six patients completed all 12 weeks of this study. The major clinical parameters measured were intraocular pressure (IOP), conjunctive hyperemia, superficial punctate keratopathy and hyperpigmentation of eyelid at baseline, 4, and 12 weeks. Additionally noted were adverse events and patient preferences, measured using a questionnaire at study initiation and at 12 weeks.Results: At baseline, IOPs were (Group A: 14.1 ± 2.9 mmHg, B: 14.5 ± 2.9 mmHg; P = 0.658), (Group A: 13.8 ± 2.6 mmHg, B: 14.3 ± 2.8 mmHg; P = 0.715) at 4 weeks, and (Group A: 14.1 ± 2.7 mmHg, B: 14.2 ± 2.7 mmHg; P = 0.538) at 12 weeks. Among the groups, there was no significant difference at any time point after baseline (P = 0.923, 0.951, respectively). All adverse events were not remarkably different after therapy. In regards to patient preference before and after switching therapy, 10 patients (50%) in Group A and 10 patients (63%) in Group B preferred using fixed-combination eye drop therapy.Conclusions: Effectiveness and safety were maintained in both groups after switching therapy. Overall, patients generally preferred using a fixed-combination therapy.Keywords: glaucoma, latanoprost–timolol, dorzolamide–timolol, brinzolamide, fixed combination, intraocular pressure